(untitled) (Journal of Basic and Applied Research in Biomedicine, 2022)
Fish bioconcentration factors (BCF) are used for the prediction of the environmental effects of new chemicals and some studies have suggested that they can be predicted from the Physico-chemical properties of the chemical. The rigorous use of pesticides resulted in the dispersal and persistence of pollutants throughout the ecosystem. Pesticides contamination in the aquatic ecosystem has become one of the most staggering issues due to their detrimental effect on public health and the environment. This study aimed to investigate the bioconcentration factor of pesticides monocrotophos and quinalphos in three tissues (skin, muscles, gills) of the fish Channa striatus for 21 days, of the three analyzed tissues of monocrotophos exposed fish, gill accumulated highest concentration of (0.033 mg kg-1) while muscles (0.012 mg kg-1) at the lowest, whereas the concentration of quinalphos was maximum (0.98mg kg-1) in liver and minimum (0.074 mg kg-1) in muscle. Results showed that the effect of pesticide differs from tissue to tissue. However, the levels exceeded maximum detection limits as recommended by U.S. Geological Survey National Water Quality Laboratory, Denver, Colo. Hence it is suggested that the fish containing pesticide residues beyond permissible limit should be avoided for food purposes